Developing Disaster Mitigation Educational Media Based on Local Folktales: Interactive Books for Children in Disaster-Prone Areas - Ambarita, Alexa Celine; Aisyabilla, Fatiha Yasmin; Widiastuti, Arum; Syabiniyah, Nuranisa; Naafi'a, Muhammad Ilman (Universitas Negeri Yogyakarta, 2026)
Background: Indonesia is a disaster-prone region, yet existing disaster mitigation education media are often unengaging and lack contextual relevance for young children. Objectives: This study aimed to develop an interactive storybook entitled